2020
DOI: 10.1002/lary.28760
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Postoperative Disposition Selection in Pediatric Otolaryngology Patients: A Novel Approach

Abstract: Objective Pediatric patients undergoing surgery on the aerodigestive tract require a wide range of postoperative airway support that may be difficult predict in the preoperative period. Inaccurate prediction of postoperative resource needs leads to care inefficiencies in the form of unanticipated intensive care unit (ICU) admissions, ICU bed request cancellations, and overutilization of ICU resources. At our hospital, inefficient utilization of pediatric intensive care unit (PICU) resources was negatively impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Interestingly, Theilhaber et al found that the majority of severe adverse events occurred within 2 hours of surgery 21 and suggested that children with CP could be monitored in the PACU for 2 hours following AT and ICU admission could be reserved for children who develop severe adverse events during that period. A previous study has shown that implementing a “gray zone,” where complex children were monitored in the PACU for 2 to 5 hours before transfer to the appropriate level of care, reduced the number of unplanned ICU admissions 39 . Children with CP with an otherwise uneventful postoperative course could be safely transferred to the ward, provided that rapid ICU response was available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Theilhaber et al found that the majority of severe adverse events occurred within 2 hours of surgery 21 and suggested that children with CP could be monitored in the PACU for 2 hours following AT and ICU admission could be reserved for children who develop severe adverse events during that period. A previous study has shown that implementing a “gray zone,” where complex children were monitored in the PACU for 2 to 5 hours before transfer to the appropriate level of care, reduced the number of unplanned ICU admissions 39 . Children with CP with an otherwise uneventful postoperative course could be safely transferred to the ward, provided that rapid ICU response was available.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that implementing a "gray zone," where complex children were monitored in the PACU for 2 to 5 hours before transfer to the appropriate level of care, reduced the number of unplanned ICU admissions. 39 Children with CP with an otherwise uneventful postoperative course could be safely transferred to the ward, provided that rapid ICU response was available. This graduated approach to postoperative disposition planning is intriguing, particularly as resources and bed availabilities are increasingly constrained but dedicated prospective studies and quality improvement initiatives will be required.…”
Section: Postoperative Dispositionmentioning
confidence: 99%
“…Surgeons are required to balance the need to avoid unnecessary costly PICU admission with the desire to prevent adverse respiratory events requiring urgent escalation of care, which are associated with a worse prognosis. 5,6 Suggested criteria for PICU admission include “very severe” OSA (defined as AHI ≥ 30/hour), complex medical history predisposing the patient to airway obstruction, age<2 years, intraoperative respiratory complications requiring treatment, and desaturations in the immediate post-operative period. 1,4,7,8…”
Section: Introductionmentioning
confidence: 99%
“…At-risk patients who only require closer monitoring and simple therapies rather than invasive organ support could be managed in this setting for a certain period of time and would obviate the need for ICU care. [17] …”
Section: Discussionmentioning
confidence: 99%
“…At-risk patients who only require closer monitoring and simple therapies rather than invasive organ support could be managed in this setting for a certain period of time and would obviate the need for ICU care. [17] Patients who required unplanned ICU admission postoperatively were found to need respiratory support in the form of supplemental oxygen or mechanical ventilation. [12,13] This is in keeping with the fact that the reason for ICU admission was commonly respiratory related.…”
Section: Discussionmentioning
confidence: 99%